The Practice of Al-Ighraq fil-atsman in the Burn Rate Strategy of Startups in Indonesia - Lia Indah Khilmina; M. Wahab Khasbulloh (Afaquna: Jurnal Cakrawala Islam, 2026)
The "burn rate" strategy has become a tool for accelerating market dominance for startups in Indonesia, but this practice often triggers indications of extreme loss-making. This study aims to examine this phenomenon through the lens of Sharia Economic Law, specifically the concept of Al-Ighraq fil-atsman. Using normative legal research methods and a conceptual approach, this study evaluates whether price efficiency in the digital ecosystem aligns with the principles of fairness in transactions. The results indicate that the systematic practice of Al-Ighraq fil-atsman to eliminate competitors (MSMEs) contains elements of dharar (harm) and market distortion, which are prohibited in Islam. Although startups claim to promote themselves, strategies that lead to monopoly (ihtikar) contradict the spirit of healthy business competition (al-munafasah al-syarifah). The conclusion of this study emphasizes that the legality of the burn rate under Sharia depends on the absence of intent to damage market prices and the protection of the rights of small producers to achieve economic balance (tawazun).